Activated script analysis an integrative approach to play analysis through creative expression and devised theatre - Horn, Elizabeth Brendel (Routledge, 2023)
Activated Script Analysis engages theatre students in traditional formative script analysis through a fusion of devised theatre and various modes of creative expression, dispelling the notion of script analysis as an isolated pen-to-paper task and reimagining it as a captivating and collaborative process. This book uses diverse, contemporary plays to model the script analysis process for each of four Theatrical Elements: Given Circumstances; Character; Setting; and Structure. By considering each of these elements, readers can uncover patterns and themes within a dramatic text. Woven throughout the study of each Theatrical Element are "Connections": Personal Connections, which encourage a reader to explore a theatrical element within their own lives, as though their lives were a script; Play Connections, which make concrete abstract ideas presented in script analysis through theatre-based play; Professional Connections, which examine how a theatre professional might analyze a script for a theatrical element within their own work; and Performative Connections, which provide the opportunity for students to explore a theatrical element through performance using devised theatre strategies. At the end of each chapter, readers are given the opportunity to analyze a text through the lens of a Theatrical Element, and to express their findings through a variety of digital, written, visual, and performance-based modes of expression. Activated Script Analysis is designed for undergraduate theatre students and educators, to be used as the primary text in Script Analysis coursework, or as a supplemental text in Acting or Directing courses"-- Provided by publisher.